STEM-04. PLATELETS DRIVE GLIOBLASTOMA ONCOGENESIS BY ENHANCING THE GLIOMA STEM CELL PHENOTYPE. (9th November 2020) - Sloan, Anthony; Lee-Poturalski, Christine; Elder, Theresa; Harris, Peggy; Cioffi, Gino; Raghavan, Alankrita; Willis, John; Rich, Jeremy; Kerstetter-Fogle, Amber; Barnholtz-Sloan, Jill S; Jankowsky, Eckhard; Sloan, Andrew E
Abstract: Glioblastoma (GBM) is recognized as one of the deadliest forms of cancer, despite aggressive therapy consisting of maximal surgical resection followed by concurrent radiation and chemotherapy, the median survival remains ~12 months. Glioma stem cells (GSCs) possess potent tumor-initiating properties and comprise a cellular hierarchy that is responsible for treatment resistance and progression. Specifically targeting GSCs has been considered a promising therapeutic approach, however no clear method has been identified. Histologically, it is known that GSCs are found in perivascular and pseudsopalisading regions of GBM. Similarly, platelet aggregates are often found in pseudsopalisading necrotic regions, suggesting a potential interaction between platelets and GSCs due to their spatial locations. High platelet counts have been associated with poor clinical outcome in many cancers including ovarian and endometrial cancer. While platelets are known to affect progression of other tumors, mechanisms by which platelets influence GBM oncogenesis are unknown. Our work aimed to understand the crosstalk between GSCs and platelets within GBM solid tumors that work to enhance disease progression and treatment resistance. Our clinical studies suggest elevated platelet counts positively correlate with tumor growth and negatively correlate to overall patient survival. We found platelets and GSC co-localization in GBM solid tissue; platelet exposure to GSCs results in increased proliferation of GSCs specifically, by increasing the self-renewing capacity of GSCs in a dose dependent manner, and resulted in an increased "Stem-like" transcriptional pattern. Inhibiting the GSC-platelet interaction results in a decrease in GSC renewal and stemness. These results introduce a novel interaction between GSCs and platelets and elucidate a novel therapeutic approach specifically targeting GSCs by disrupting the GSC-platelet interaction.